Soil–structure interaction analysis of a FPS-isolated structure using finite element model. (February 2016) - Krishnamoorthy, A.; Anita, S.
Abstract: A numerical model for the seismic analysis of a structure isolated with friction pendulum system (FPS) considering soil structure interaction (SSI) is developed. In the analysis, the soil is considered as an elastic continuum and is modeled using finite element method. Three degrees of freedom (two translational and one rotational) are considered for the structure whereas the soil is modeled using plane strain element with two translational degrees of freedom. Sliding and non-sliding phases of FPS are modeled using a fictitious spring. Effects of considering soil structure interaction on a multi-degree-freedom structure isolated with friction pendulum system is investigated using the proposed method. A parametric study is also carried out to investigate the influence of flexibility of soil, type of earthquakes, frequency content of earthquake ground motions, friction coefficient of sliding material, isolation time period, number of floors and the time period of fixed base structure on the response of isolated structure with SSI. The results of the numerical study show that the SSI affects the response of the structure isolated with FPS and in many cases, the response of the structure increases due to SSI.